Kıbrıs’ın Güneyinden Kuzeyine Göç Eden Kıbrıslı Türklerin Kuzeyde Doğan Çocuklarının Aile İçi Sözlü Anlatımlarla Oluşan Kıbrıslı Türk-Rum İlişkileri Algısı / The Perceptions among the Children Born in the Northern Cyprus from the Turkish Cypriot Families Immigrated from the Southern Part of Cyprus to the North on the Relations of Turkish Cypriot-Greek Cypriot through the Family Statements - Dolunay, Ayhan; Keçeci, Gökçe; Kasap, Fevzi (Journal of History Culture and Art Research, 2017)
Abstract The Ottoman citizens together with the local community had generally lived a peaceful life in Cyprus, conquered by the Ottoman Empire in 1571, until the island was handed over to the England in 1878. Following such period and subsequent process, the Turkish Cypriots and Greek Cypriots continued to live together in the island until the foundation of Republic of Cyprus in 1960; yet, with the impact of British policies, the Turkish and Greek Cypriot communities had started to disintegrate. In 1950s, the island began to lose its nature and the concept of living together peacefully was disappeared due to the armed attacks of Greek Cypriots launched within the scope of underground military organisation and the responses of Turkish Cypriots through their underground military organisations together with the limited resources. The events, which stopped with the foundation of 1960 Republic of Cyprus, had become more severe following the obligatory leave of Turkish Cypriots from the partnership republic in 1963, and continued until the military intervention of Turkey in 1974 and both communities had losses, more in the Turkish Cypriot side. Until 1950s to 1974, the Turkish Cypriots, who did not feel secure in the southern part of island, migrated to the northern part of island. The relevant immigrants had shared their common lives with the Greek Cypriots before 1950s and then the following conflicts through oral narratives to their children born in the northern part of Cyprus; therefore, the perceptions of children of migrated families were only shaped with the narrations and some written references since a direct communication was not possible particularly until the opening of border crossing points. The original value of this study is the non-availability of any oral history research on the Turkish-Greek Cypriot relations before 1974 conducted with the generation after 1974; the aim of this research is to identify the perceptions of Turkish Cypriots born in the northern part of Cyprus mainly after 1974 that was shaped within the framework of oral narrations within the families through the individual interviews with the reference people sharing their experiences within the history via the press screening for the identification of social-political structure during the historical process, and the formation of such perceptions through the interviews. Öz 1571’de Osmanlı İmparatorluğu’nca fethedilen Kıbrıs’ta, Osmanlı vatandaşları ile, yerli halk, 1878’de ada İngiltere’ye kiralanana kadar, bir arada, genel olarak huzurlu bir yaşam sürmüşlerdir. 1878’de, adanın İngiltere’ye kiralanması ve izleyen süreçte adada, 1960 Kıbrıs Cumhuriyeti kurulana değin, Kıbrıslı Türkler ve Kıbrıslı Rumlar, bir arada yaşamaya devam etmiş ancak, İngiliz yönetiminin politikalarının da etkisi ile, Türk ve Rum toplumları süreç içerisinde ayrışmaya başlamıştır. 1950’li yıllarda, önce Kıbrıslı Rumlarca yer altı askeri yapılanma kapsamında başlatılan silahlı saldırılar ve Kıbrıslı Türklerin kendilerini müdafaa kapsamındaki yer altı askeri yapılanmaları aracılığıyla ve kısıtlı imkanlarla verdiği karşılıklarla birlikte, adada kayıplar yaşanmış, bir arada huzurlu yaşam olgusu yitirilmiştir. 1960 Kıbrıs Cumhuriyeti’nin kurulması ile duran olaylar, 1963’de Kıbrıslı Türklerin ortaklık cumhuriyetinden ayrılmak zorunda kalmasının akabinde, yeniden şiddetlenmiş ve Türkiye’nin adaya 1974’de gerçekleştirdiği askeri müdahaleye kadar sürmüş; Kıbrıslı Türk toplumundan daha fazla olmak üzere, iki toplum da kayıplar vermiştir. 1950’lerden, 1974’e kadar, çatışmalar nedeniyle, adanın güneyinde kendilerini güvende hissetmeyen Kıbrıslı Türkler, adanın kuzeyine göç etmiştir. İlgili göçmenler, Rum toplumu ile 1950’ler öncesi ortak yaşamlarını ve sonrasındaki çatışmaları sözlü anlatımlarla, adanın kuzeyinde doğan çocuklarına aktarmış; özellikle 2003 yılında sınır kapıların açılmasına kadar, doğrudan iletişimin mümkün olamaması nedeniyle, göç eden neslin çocuklarının algısı, sadece anlatımlar ve bazı yazılı kaynaklar ile şekillenmiştir. 1974 sonrası doğan nesil ile daha önce, 1974 öncesi Türk-Rum ilişkileri hakkında sözlü tarih araştırması yapılmamış olması, çalışmanın özgün değerini ortaya koyarken; çalışmada, tarihsel süreçteki deneyimlerini aktaracak kaynak kişilerle gerçekleştirilen bireysel görüşmeler ve yine tarihsel süreçteki sosyal-siyasi yapıyı tespit adına basın taraması ile birlikte, temel olarak, 1974 sonrası kuzeyde doğan Kıbrıslı Türklerin, aile içi sözlü anlatımlar çerçevesinde şekillenen ilgili algılarının, gerçekleştirilecek mülakatlar ile şekillendiğinin tespiti hedeflenmektedir.